2007
DOI: 10.1007/s11255-006-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult Wilms’ tumor: A case report and review of literature

Abstract: We report the case of a 43-year-old woman with adult Wilms' tumor. Imaging studies confirmed the presence of a 25 x 20 x 12 cm mass in the left kidney. A radical transabdominal nephrectomy was performed. Histological diagnosis was adult Wilms' tumor. Postoperative chemotherapy was offered to the patient who remains disease-free 67 months postoperatively. There are a few reported cases of this entity and till today the best treatment options and the prognosis remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The 2 primary multi-institutional Wilms' tumor cooperative groups, the National Wilms Tumor Study Group (NWTS) and the International Society of Paediatric Oncology (SIOP), have each published analyses of adult Wilms' tumor cases registered on their respective trials. 19,20 The publications from these groups were based on adult (!16 years) subsets that were treated identically to the children on protocol with overall and disease-free survival results comparable to those of the children.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The 2 primary multi-institutional Wilms' tumor cooperative groups, the National Wilms Tumor Study Group (NWTS) and the International Society of Paediatric Oncology (SIOP), have each published analyses of adult Wilms' tumor cases registered on their respective trials. 19,20 The publications from these groups were based on adult (!16 years) subsets that were treated identically to the children on protocol with overall and disease-free survival results comparable to those of the children.…”
Section: Introductionmentioning
confidence: 99%
“…Small case series, single institution experiences, and population based studies have reported significantly worse survival for adult WT than pediatric WT. 2,5,[11][12][13][14][15][16][17][18] In contrast, multi-institutional cooperative WT studies have reported comparable outcomes to that of children when patients are treated with protocol-driven, risk-stratified, multimodal therapy. 19,20 Given the conflicting data available, this study sought to evaluate WT treatment patterns and outcomes based on age using data captured by the NCDB, a large national database that captures patients across all ages, not just those enrolled on study.…”
Section: Discussionmentioning
confidence: 99%
“…Wilms' tumor or nephroblastoma is a malignant embryonal tumor of the kidney made up of embryonic cells and commonly found among children below five years old [1] , [2] . It is infrequent in adults and usually has poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is infrequent in adults and usually has poor prognosis. Adult Wilms' tumor can be diagnosed using criteria outlined by Klinton et al such as 1) tumor is identified as primary renal neoplasm 2) presence of primitive blastemic spindle or round cell component 3) formation of abortive or embryonal tubules or glomerular structures 4) absence of renal cell carcinoma around tumor area 5) histologically confirmed 6) age above 15 years old [2] .…”
Section: Introductionmentioning
confidence: 99%